Use of Media Zoom to Improve Thematic Learning Results About Night-Night Activities In Class 1 Students - Purnamasari, Dhesi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this research is to improve student learning outcomes in thematic material about night activities. This research is a classroom action research (PTK) which is carried out in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were the first grade students of SDN Tambakreja 07 in the 2020/2021 academic year, totaling 28 students. Data collection techniques using observation and tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the use of Zoom media can improve student learning outcomes on thematic material about nighttime activities in class I SDN Tambakreja 07 academic year 2020/2021 as evidenced by the percentage of completeness of learning outcomes in cycle I of 53.57% to 75% in cycle II